(3GdeYQH hGdONjds - (3GdeOfj , eUWaj GdeOfjs
(3ChdgG (B:s
(3GHQGgje GSe CYLei ajg dZGJ EHQGgGe hGHQGgje eKdKI GdaGA CHQgI GSe CYLei s
(3BNQgG (B:s
(3bGd GdLhGdjbi (B: (3CYLei eYQH efShH Edi jghP Hf jYbhH aYQH HEgeGd GdPGd(B: (3GfJgi s
(3cJHJ GdehGO HGdMeQI ade JXgQ hGVMI YfO GdJUhjQs
(3cJHJ HNW ajg VHWs
(3eQJH Ydi MQha GdeYLes
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B287s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B238 s
Keywords: (3GdeYGQa GdYGeIs